Wednesday

April 16, 2014

April 16, 2014

Posted by **mic** on Saturday, August 28, 2010 at 9:58pm.

- geometry -
**MathMate**, Saturday, August 28, 2010 at 10:07pmRearrange equation into:

3x²-x + 6x-2

=x(3x-1) + 2(3x-1)

=(x+2)(3x-1)

or use the quadratic formula,

or by completing squares.

- geometry -
**mic**, Saturday, August 28, 2010 at 10:09pmhow did you get the 6x?

- geometry -
**MathMate**, Saturday, August 28, 2010 at 10:12pm5x = -x + 6x

**Related Questions**

math - 3xsquared + 27 = 5 3xsquared -5x = -3xsquared + 6 SOLVE

geometry - solve for x: 3xsquared+5x=2

college algebra - h(x)=3xsquared+5x-3

math check my answers - 1. 2(x+3)squared-6x+5=0 Answer= 2xsquared+6x+23=0 2. ...

ALGEBRA - Evaluate the expressions: 1. -8x when x=6 2. 3xsquared-5x when x=-2 3...

algebra 2 - SImplify the expressions. 1. x to the seventh times 1/x squared 2. (...

geometry - Which equation is the correct equation to solve for x? Given ST = 5x...

Geometry - Reiny, according to this problem(one side of a triangle is x inches ...

Geometry - Distributive Property: -3(5x - 2) -3 (5x) (-2) -15x + 6 = x - 9 Is ...

geometry - how to decide whether lines with the given equation are parallel, ...